Comparative Study of Bioactive Compounds in Different Varieties of Pears in Nepal - Koirala, Barsha; Shrestha, Angela (Nepal Journal of Biotechnology, 2020)
This study was conducted to evaluate the physicochemical parameters, perform qualitative tests (for sugars and phytochemicals), and quantitative tests (phenolics, antioxidants, anthocyanins, tannins, vitamin C) of six different varieties of pears i.e. Bartlette, Chinese pears, Chojuro, Kosui, Pharping local, and Yakumo. The juices extracted from respective pears were used for the analysis. The phenols were determined by the Folin-Ciocalteu method, antioxidants by the DPPH scavenging activity, and anthocyanins by a SO2 bleaching technique. The Pharping local pears were found to have the highest anthocyanins (85.95±0.1 mg/l), total phenolic content (600±0.01 mg GAE/l), antioxidants (IC50 value 250±0.00 mg of phenol/l) and vitamin C content (12.2±0.01 mg/100 ml) and tannins were observed to be highest in Yakumo pears (0.93±0.01 g/l). Likewise, the highest clarity i.e. 1.960±0.00 was observed in Bartlette pears and the highest acidity (2.01±0.01%) in Chojuro pears. Various sugar/carbohydrate tests like Molisch’s test, Benedict’s test, Barfoed test, Bial’s test, Seliwanoff test, Fehling’s test and Iodine test were performed for the pear varieties. All the pears gave positive results for all the sugar tests except Iodine test. The positive results for sugar/carbohydrate signifies the presence of various sugars that help for the better taste, texture, and aroma of pear. The pear varieties showed the presence of phytochemicals like flavonoids, terpenoids, catechins, cyclic glycosides, and proteins. The phytochemicals are responsible for fruit preservation and act as anti-carcinogenic components. Among the varieties of pears, Pharping local pears were observed to be most nutritional because of high antioxidants, phenols, anthocyanins, and vitamin C.